Multi-echelon, multi-indenture spare parts inventory control subject to system availability and budget constraints - Costantino, Francesco; Di Gravio, Giulio; Tronci, Massimo (Reliability engineering & system safety, 2013)
Inventory management of spare parts is one of the most critical issues in the aeronautical industry, given the required level of system availability related to the strategic importance and high stocking costs of the components. Even if a large number of spare parts increases warehousing costs, every single shortage have a greater impact: the adoption of best-in-class inventory management techniques becomes crucial. On these considerations, the paper presents an innovative model of spare parts allocation for the Italian Air Force with the aim of minimizing backorders and, at the same time, ensuring an availability of 99% depending on the actual flight plan. The model, solved by a marginal analysis, considers an original configuration of features combining different skills of maintenance centers in a hierarchical multi-echelon, multi-item, multi-indenture structure. A real case is provided in order to analyze the solving method and the results. •We studied a problem of allocations for spare parts of aeronautical systems.•The model presents different repair capabilities of maintenance centers.•The model fits constraints on budget and on total operational availability.•The model is solved by a marginal analysis with a backorder/price ratio.•A numerical example shows a spare parts allocation with relative considerations.